Act local Think global. - van Weelden, Dirk; Koch, H.; Jansen, Theo; Broodthaers, Marie-Puck; Tarantino, Michael; Kleerebezem, Jouke (Rotterdam : Stichting Still, 1992)
Serafijn, Q.S. ; Roosen, Maria ; van Ham, Milou ; Winters, Robin ; Finke, Francy ; Kliest, A.F.
Act local Think global, Stichting Still, Rotterdam, Project 381B (presentatie van werken / lezingen/publikatie)
boek